Combustion and incineration processes appl-ications in environmental engineering - Niessen, Walter R. (Environmental science and pollution control series, 1995)
This work covers the techniques required to interpret field data, critique and/or develop combustion designs, and evaluate proposed alternatives. This second edition presents new material on areas including air pollution control technology, and basic waste combustion processes.